2004
DOI: 10.1007/s10152-004-0173-7
|View full text |Cite
|
Sign up to set email alerts
|

Codium fragile: rhizomatous growth in the Zostera thief of eastern Canada

Abstract: A rhizomatous growth form of Codium fragile is described for the first time. Plants were collected in the Gulf of St. Lawrence in estuaries dominated by Zostera marina. Rhizomatous plants developed from propagules of whole plants that settled horizontally. Horizontal axes of C. fragile were up to 1 m long in plants collected in situ. Plants developed several to dozens of erect axes at right angle to the base. Horizontal growth of up to 0.2 m was found in field experiments where fragments were tied to plastic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…tomentosoides; Provan et al 2008), hereafter Codium, is usually associated with hard substrata habitat. However, in the southern Gulf of St. Lawrence, eastern Canada, where Codium has recently established (Lyons & Scheibling 2009), this alga demonstrates great ecological plasticity such that it can also settle and grow on eelgrass rhizomes, allowing it to successfully establish populations in soft-sediment habitats (Garbary et al 2004). High densities of Codium were found in eelgrass Zostera marina beds in îles de la Madeleine, southern Gulf of St. Lawrence, in 2003 (Simard et al 2007), and Codium has since persisted and expanded.…”
Section: Introductionmentioning
confidence: 99%
“…tomentosoides; Provan et al 2008), hereafter Codium, is usually associated with hard substrata habitat. However, in the southern Gulf of St. Lawrence, eastern Canada, where Codium has recently established (Lyons & Scheibling 2009), this alga demonstrates great ecological plasticity such that it can also settle and grow on eelgrass rhizomes, allowing it to successfully establish populations in soft-sediment habitats (Garbary et al 2004). High densities of Codium were found in eelgrass Zostera marina beds in îles de la Madeleine, southern Gulf of St. Lawrence, in 2003 (Simard et al 2007), and Codium has since persisted and expanded.…”
Section: Introductionmentioning
confidence: 99%
“…The ephemeral nature of high Codium cover coupled with the time lag between low and high Codium cover could provide sufficient time for eelgrass recovery in invaded patches and thus reduce the impact of the Codium on eelgrass beds. A concomitant effect of unstable Codium patches is that when large thalli are dislodged, they may take along portions of the rhizomes, and hence the alga's latest nickname, ''eelgrass thief'' (Garbary et al 2004), a variant of the more traditional one, ''oyster thief''. This phenomenon may lead to the disruption of the rhizome mat, isolating shoots such that they can no longer benefit from physiological assistance by older shoots and subsequently may be more affected by stress, e.g., light limitation (Tomasko and Dawes 1989).…”
Section: Experiments Versus Patterns In Natural Invaded Bedsmentioning
confidence: 99%
“…Indeed, it is often considered to be one of the most notorious seaweed invaders in the world (Trowbridge 1998) even though few studies have rigorously examined its environmental impacts (but see Levin and Hay 2002;Scheibling and Gagnon 2006;Schmidt and Scheibling 2007;Drouin et al 2011). Although typically associated with hard substrates, including both rocky substrata and shells, this large seaweed is also able to epiphytically colonize exposed seagrass rhizomes (Garbary et al 2004), growing as long as or longer than the plants with which it is associated (authors, personal observations). Earlier studies suggested that Codium was a poor competitor for resources with native seagrass in soft-bottom habitats, due in part to the limited availability of hard substrata (Malinowski and Ramus 1973) and a greater vulnerability to environmental conditions in lagoonal systems relative to native algae (Thomsen and McGlathery 2007).…”
Section: Introductionmentioning
confidence: 95%
“…Several anthropogenic vectors have been implicated in local and long-distance dispersal of C. fragile: growth on boat hulls and propellers, attachment to bivalve shells, use as packing material in fishery products, and fouling of fishing nets (Carlton and Scanlon 1985). Once established, C. fragile has various modes of asexual reproduction and natural dispersal: it produces parthenogenetic swarmer cells that settle within hours (Borden and Stein 1969;Churchill and Moeller 1972;Fralick and Mathieson 1973), as well as vegetative buds and thallus fragments, that are dispersed by currents and can attach to hard substrata to form new thalli (Fralick and Mathieson 1972;Garbary et al 2004;Scheibling and Melady 2008;Watanabe et al 2009). Detached whole thalli of C. fragile also can act as dispersal agents, either floating with surface currents or drifting along the seafloor (Dromgoole 1982;Scheibling and Melady 2008;Watanabe et al 2009).…”
Section: Introductionmentioning
confidence: 99%